And There He Kept Her - Moehling, Joshua (Naperville, Illinois : Poisoned Pen Press, 2022)
"When misguided teenagers Jesse Crawford and Jenny Wheeler are forced to rob Emmett Brown to escape impossible circumstances, what starts as a home invasion quickly turns into a nightmare for the teens. What Jesse and Jenny dont know is that although Emmett is now old, severely obese, and in chronic pain, Emmett was responsible for the kidnapping and deaths of two young women almost twenty years ago, crimes that have never been solved. So Emmett is quick to turn the tables, blurring the lines between who the real victim is here. Ben Packard, a sheriffs deputy and former Minneapolis cop who fled the Twin Cities after his boyfriend was killed in the line of duty, is leading the investigation into the missing teens with a keen sense of urgency because Jenny is his cousins daughter. Bens been living like a monk in the small town of Sandy Lake for almost two years, battling to keep his private life private while moving up the ranks of the sheriffs department. But the more he works this case, the more hes forced to unveil his own secrets, and in turn the dark pasts of the people hes sworn to serve"--
Keywords: Burglary -- Fiction; Detective and mystery fiction; Novels; Detective and mystery fiction